The principles of banking - Choudhry, Moorad (John Wiley & Sons Singaphore, 2012)
The Principles of Banking reiterates that theprimary requirement of banking—sound capital and liquidityrisk management—had been forgotten in the years prior to thefinancial crash. Serving as a policy guide for market practitionersand regulators at all levels, the book explains the keys to successthat bankers need to follow during good times in order to beprepared for the bad, providing in-depth guidance and technicalanalysis of exactly what constitutes good banking practice.